Diabetes- and angiotensin II-induced cardiac endoplasmic reticulum stress and cell death: metallothionein protection - Xu, Jiancheng (Blackwell Publishing Ltd, 2009)
We have shown cardiac protection by metallothionein (MT) in the development of diabetic cardiomyopathy (DCM) via suppression of cardiac cell death in cardiac-specific MT-overexpressing transgenic (MT-TG) mice. The present study was undertaken to define whether diabetes can induce cardiac endoplasmic reticulum (ER) stress and whether MT can prevent cardiac cell death via attenuating ER stress. Diabetes was induced by streptozotocin in both MT-TG and wild-type (WT) mice. Two weeks, and 2 and 5 months after diabetes onset, cardiac ER stress was detected by expression of ER chaperones, and apoptosis was detected by CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP) and cleaved caspase-3 and caspase-12. Cardiac apoptosis in the WT diabetic mice, but not in MT-TG diabetic mice, was significantly increased 2 weeks after diabetes onset. In parallel with apoptotic effect, significant up-regulation of the ER chaperones, including glucose-regulated protein (GRP)78 and GRP94, cleaved ATF6 and phosporylated eIF2α, in the hearts of WT, but not MT-TG diabetic mice. Infusion of angiotensin II (Ang II) also significantly induced ER stress and apoptosis in the hearts of WT, but not in MT-TG mice. Direct administration of chemical ER stress activator tunicamycin significantly increased cardiac cell death only in WT mice. Pre-treatment with antioxidants completely prevented Ang II-induced ER stress and apoptosis in the cultured cardiac cells. These results suggest that ER stress exists in the diabetic heart, which may cause the cardiac cell death. MT prevents both diabetes- and Ang II-induced cardiac ER stress and associated cell death most likely via its antioxidant action, which may be responsible for MT's prevention of DCM.